Defining the hydrophobic interactions that drive competence stimulating peptide (CSP)-ComD binding in Streptococcus pneumoniae - Koirala, Bimal; Hillman, Robert A.; Tiwold, Erin K.; Bertucci, Michael A.; Tal-Gan, Yftah (Beilstein Journal of Organic Chemistry, 2018)
Quorum sensing (QS) is a cell–cell communication mechanism that enables bacteria to assess their population density and alter their behavior upon reaching high cell number. Many bacterial pathogens utilize QS to initiate an attack on their host, thus QS has attracted significant attention as a potential antivirulence alternative to traditional antibiotics. Streptococcus pneumoniae, a notorious human pathogen responsible for a variety of acute and chronic infections, utilizes the competence regulon and its associated signaling peptide, the competence stimulating peptide (CSP), to acquire antibiotic resistance and establish an infection. In this work, we sought to define the binding pockets within the ComD1 receptor used for binding the hydrophobic side-chain residues in CSP1 through the introduction of highly-conservative point mutations within the peptide. Optimization of these binding interactions could lead to the development of highly potent CSP-based QS modulators while the inclusion of non-natural amino acids within the CSP sequence would confer resistance to protease degradation, a requirement for drug candidates.
Keywords: binding surface; competence stimulating peptide (CSP); protein–peptide interactions; quorum sensing; Streptococcus pneumoniae; structure–activity relationships (SAR)